I Consider Intervening in the Structure of a Film Unthinkable. An Interview with Blazena Urgosikova - Frodlova, Tereza (Iluminace, 2013)
An interview with film historian and archivist Blazena Urgosikova about film restoration and its beginnings in the Czech Republic.
Keywords: film historians; digital restoration; film restoration; Narodni filmovy archiv